2019
DOI: 10.5296/jfi.v3i1.15721
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hot Air Thin Layer Drying Temperature on Physicochemical and Textural Properties of Dried Horseradish

Abstract: The horseradish (Armoracia rusticana) is an important crop as ingredients for many commercial food products and medicinal uses. However, the horseradish is perishable and preservation of this crop for supplying year-round is necessary. Drying can be used to preserve the horseradish but establishing a suitable drying method and conditions are important for product quality of dried horseradish. The objective of this study was to investigate the effects of hot air-drying temperatures on the physicochemical and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…The higher drying temperature decreased the drying time of the samples to reach to an equilibrium moisture content. These results were in the agreement with other studies (Meda et al, 2016;Midilli & Kucuk, 2003;Mitra et al, 2019;Orsat et al, 2006). This study indicated that the constant drying rate periods were 150, 220 and 280 minutes and complete drying times were 300, 350 and 400 minutes (Figure 1) for horseradish samples dried at 85, 70 and 50℃, respectively.…”
Section: Effect Of Drying Temperature and Blanching On The Drying Kinetic Of Horseradishsupporting
confidence: 93%
See 4 more Smart Citations
“…The higher drying temperature decreased the drying time of the samples to reach to an equilibrium moisture content. These results were in the agreement with other studies (Meda et al, 2016;Midilli & Kucuk, 2003;Mitra et al, 2019;Orsat et al, 2006). This study indicated that the constant drying rate periods were 150, 220 and 280 minutes and complete drying times were 300, 350 and 400 minutes (Figure 1) for horseradish samples dried at 85, 70 and 50℃, respectively.…”
Section: Effect Of Drying Temperature and Blanching On The Drying Kinetic Of Horseradishsupporting
confidence: 93%
“…vitamins, minerals and fibers etc.). Horseradish is a vital crop which is being used as food ingredients for many commercial food products such as sauces and condiments (Mitra, Alim, & Meda, 2019). So, the horseradish has been an important crop in parts of Europe and significant production also exists in the U.S and Canada.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations